Presidential Rhetoric and Populism. Issue 2 (26th April 2020) - Çinar, Ipek; Stokes, Susan; Uribe, Andres
Abstract: Scholars and the general public have been struck by the norm‐shattering rhetoric of President Donald J. Trump. His "rhetorical signature" is heavy with Manichean good‐versus‐evil messages, vilification of his opponents, and disdain for institutions and for evidence. But many politicians vilify their opponents and style themselves as uniquely able to solve their society's problems. In fact, Trump's Manichean discourse is typical of populist leaders, in the United States and around the world. Using text‐as‐data analysis of campaign rhetoric, we study the content and mood of presidential campaign speeches by a range of U.S. politicians, which allows a broader perspective not only on the uniqueness of Trump's rhetoric, but also its continuities with the rhetoric of others. This analysis allows us to define Trump as a right‐wing populist. Right‐wing populists, like left‐leaning ones, are anti‐elitist and Manichean in words and outlook. However, the two versions of populism differ in the nature of the anti‐elitism, with right‐wing populists targeting political elites and left‐wing ones targeting economic elites. Right‐wing populists also define the "other" as ethnic out‐groups, who threaten the ethnically pure "people."